Leitores especiais de jornais: um estudo sobre estratégias de acessibilidade de pessoas cegas ao webjornalismo paraibano - Araújo, Valter Barbosa de (2015)
Based on the validation actions and skills aimed at inclusion of visually impaired people to information weighs up, through this work, accessibility, promoted by Paraiba journalism that potential reader. Throughout its history, the printed newspaper has been recording new news processes such as the Radio Journalism, TV journalism and now web journalism, which always leads to be rethinking new actions and practices to keep your audience and gain new readers. From this perspective, this study aimed to, conduct a study about web journalism in Paraíba, in order to understand the problems of accessibility of blind readers of newspapers, including aspects relating to the design of media coverage and journalistic language, based on theoretical contributions and practical techniques that involve production, circulation, distribution and reception of journalistic content. In principle a literature search was performed with selective reading and understanding of the key concepts involved in this study; then there was the application of a questionnaire to people involved in the production of web journalism and responsible for providing this content on the web (page developers, programmers and reporters); Later, an accessibility testing was done in the online versions of newspapers making sure the on specialized sites. Therefore, we used the validators that are automated tools and direct review, evaluating the web accessibility level, through research in the page code. The elements of the newspapers analyzed were: the text and the image, leading the print media work tools. Accessibility errors were identified as frequent and cross the two newspapers analyzed. Examples of the most common mistakes is highlighted links whose content is an image without alternative text and links with the same text, but different destinations. Some of these errors are obstacles to understanding the content, by people with disabilities, especially those who use assistive technologies, like the screen readers. This research is finalized with the application of an interview Focus Group involving voluntary participants, people with visual disabilities, representatives of a part of society that until the early 90s of the twentieth century, did not have any strategy for reading newspapers . In the focus group, it was observed that most of the reports collected included the internet as one of the most used communication vehicles, followed by radio in its traditional version and also the web radio.